Revisão bibliográfica acerca do trabalho pedagógico com o primeiro ano de vida dentro de berçários: uma comparação entre bases nacionais e internacionais - Garcia, Gabriela Pascoalino (Universidade Federal de São Carlos, 2022)
This article was produced for the completion of the first author's course conclusion work, whose objective was to compare two bibliographic reviews about the pedagogical work with the first year of life, both being Scientific Initiation works. The national-based research was carried out in the CAPES theses and dissertations bank between 2015 and 2019 and used “baby/babies” as descriptors, and filtered works in the field of education and educational psychology, selecting 34 works for analysis. The research on an international basis was carried out in the Web of Science database between 2014 and 2018 with the descriptors babies, toddler, early childhood, early childhood education, kindergarten and nursery, which were used grouped and separately, and the filters used were pedagogy and psychology of education, resulting in 9 articles corresponding to the theme. In the present text we present the research and dialogue with the results obtained, establishing general categories that characterize the pedagogical work with the first year of life. The results indicate the presence of relevant themes and theoretical diversity, a look from the relationships to the teaching action detached from common sense bringing the educational aspects and the intentional role of the teacher, however it points us to the lack of specificity still present in early childhood education.
Bibliographic review about pedagogical work with the first year of life in nurseries: a comparison between national and international bases
Keywords: Primeiro ano de vida; Trabalho pedagógico; Educação infantil; First year of life; Child education; Pedagogical work; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM